Magnetic data modeling applied to a zone with emerald potential in Boyacá, Colombia (2018)
A magnetic data model is developed in a zone with potential for emerald deposits in Boyacá, Colombia. In order to achieve this objective, a two-step modelling plan is followed. The first one is a forward model, which uses rectangular prism cells to represent the subsurface and let us predict the magnetic anomaly in the inference of a mineral deposit. The second one is the inversion of the data, developed using the ZondGM2D software which implements a weighted damped least squares solution through the Occam method. From the first step, the theoretical response of a proposed model of the mineralization in the place was obtained. In order to apply the second step, the ZondGM2D software was tested with synthetic data, showing the accuracy of the algorithms in terms of locating the anomaly source. Finally, the 2D magnetic susceptibility models obtained by the inversion possibly show the Itoco fault which is related with the emerald deposits of the zone.